Unsupervised machine learning and prognostic factors of survival in chronic lymphocytic leukemia. (1st June 2020) - Coombes, Caitlin E; Abrams, Zachary B; Li, Suli; Abruzzo, Lynne V; Coombes, Kevin R
Abstract: Objective: Unsupervised machine learning approaches hold promise for large-scale clinical data. However, the heterogeneity of clinical data raises new methodological challenges in feature selection, choosing a distance metric that captures biological meaning, and visualization. We hypothesized that clustering could discover prognostic groups from patients with chronic lymphocytic leukemia, a disease that provides biological validation through well-understood outcomes. Methods: To address this challenge, we applied k-medoids clustering with 10 distance metrics to 2 experiments ("A" and "B") with mixed clinical features collapsed to binary vectors and visualized with both multidimensional scaling and t-stochastic neighbor embedding. To assess prognostic utility, we performed survival analysis using a Cox proportional hazard model, log-rank test, and Kaplan-Meier curves. Results: In both experiments, survival analysis revealed a statistically significant association between clusters and survival outcomes (A: overall survival, P  = .0164; B: time from diagnosis to treatment, P  = .0039). Multidimensional scaling separated clusters along a gradient mirroring the order of overall survival. Longer survival was associated with mutated immunoglobulin heavy-chain variable region gene ( IGHV ) status, absent Zap 70 expression, female sex, and younger age. Conclusions: This approach to mixed-type data handling and selection of distance metric captured well-understood, binary, prognostic markers in chronic lymphocytic leukemia (sex, IGHV mutation status, ZAP70 expression status) with high fidelity.